2015
DOI: 10.3892/or.2015.4085
|View full text |Cite
|
Sign up to set email alerts
|

HOXA1 enhances the cell proliferation, invasion and metastasis of prostate cancer cells

Abstract: HOXA1, a member of the HOX gene family, has been implicated in tumor progression. However, the role of HOXA1 in prostate cancer is not well-established. In the present study, we found that HOXA1 was highly expressed in prostate cancer cells. We then repressed the expression of HOXA1 by short hairpin RNA (shRNA) to investigate the function of HOXA1 in prostate cancer cells. Our in vitro data showed that knockdown of HOXA1 attenuated the growth, invasion and migration of prostate cancer DU-145 and PC-3 cells. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 23 publications
1
50
0
Order By: Relevance
“…Several HOX genes were previously implicated in neoplastic transformation resulting in leukemia [23] as well as solid cancers derived from various organs [24,25]. Furthermore, the involvement of particular HOX genes such as HOXC13, HOXD3, HOXA1 in metastasis and invasiveness was recently demonstrated for melanoma, breast and prostate cancer, respectively [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Several HOX genes were previously implicated in neoplastic transformation resulting in leukemia [23] as well as solid cancers derived from various organs [24,25]. Furthermore, the involvement of particular HOX genes such as HOXC13, HOXD3, HOXA1 in metastasis and invasiveness was recently demonstrated for melanoma, breast and prostate cancer, respectively [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…It also contributes to inner and middle ear development, basioccipital bone formation and patterning of the great arteries and outflow tract of the heart (46). Over the last two decades, HOXA1 has been linked to adult cancers in breast, lung, liver, prostate and the oral cavity, as well as to melanoma (712). In the context of breast cancer, HOXA1 has been identified as a mammary epithelial oncogene, where its forced expression is sufficient to induce the oncogenic transformation of immortalized human mammary epithelial cells to aggressive in vivo carcinoma (11,13).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the gelatinase class MMPs, the expression of two other MMPs, MMP-3 and MMP-14, is activated by HOX transcription factors [62,63] . MMP-14 differs from other MMPs as it is membrane bound through a transmembrane domain with its catalytic center on the outside of the cell [64] .…”
Section: Hox Transcription Factors and Metastasismentioning
confidence: 99%
“…MMP-14 has been shown to be upregulated by HOXA3 expression [62] , and HOXA3 is overexpressed in a number of cancers, including prostate cancer [25] . Another HOX gene linked to the progression of prostate cancer is HOXA1, the expression of which promotes the proliferation, invasion and metastasis of prostate cancer cells [63] . A number of key downstream target genes of HOXA1 have been identified, including MMP-3, which has itself been linked to prostate tumor progression in a number of studies [68][69][70][71] , and polymorphisms in the MMP-3 gene have been identified as a risk factor for the development of prostate cancer [72] .…”
Section: Hox Transcription Factors and Metastasismentioning
confidence: 99%
See 1 more Smart Citation